2021
DOI: 10.1002/jcla.23943
|View full text |Cite
|
Sign up to set email alerts
|

CTR9‐mediated JAK2/STAT3 pathway promotes the proliferation, migration, and invasion of human glioma cells

Abstract: Background CTR9 (Cln three requiring 9) has been reported to be implicated in protein modification and oncogenesis of several human cancers. However, the protein expression and mechanism of CTR9 in glioma progression remain unclear. Methods We analyzed mRNA expression of CTR9 and CTR9‐related survival curves in the public database. Then, we detected CTR9 expression in glioma tissues and constructed U251 and U87 cells with stable silencing or overexpression of CTR9. Cell function tests and Western blot were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Panaxadiol inhibits proliferation, and induced apoptosis of pancreatic cancer cells, and suppresses the growth of xenograft models by suppressing the JAK2/STAT3 pathway [ 30 ]. In addition, the activation of JAK2/STAT3 pathway regulates malignant behaviors of glioma cells, including the proliferation and invasion of glioma cells [ 31 ]. A recent study showed that miR-19a can inhibit the JAK2/STAT3 pathway, thereby inhibiting cell proliferation and promoting apoptosis of SaOS-2 cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Panaxadiol inhibits proliferation, and induced apoptosis of pancreatic cancer cells, and suppresses the growth of xenograft models by suppressing the JAK2/STAT3 pathway [ 30 ]. In addition, the activation of JAK2/STAT3 pathway regulates malignant behaviors of glioma cells, including the proliferation and invasion of glioma cells [ 31 ]. A recent study showed that miR-19a can inhibit the JAK2/STAT3 pathway, thereby inhibiting cell proliferation and promoting apoptosis of SaOS-2 cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that these pathways may be inactivated in STAD, which was consistent with previous study [ 21 ]. On the contrary, HOXC10 was positively associated with IL6/JAK/STAT3 and IL2/STAT5 signaling in glioma, and previous studies also indicated that these two signaling pathways were activated [ 22 , 23 ]. We also evaluated the correlations of HOXC10 with immune infiltrations, and found that HOXC10 was positively associated with immune score in most cancers (LUAD, LUSC, TGCT, CESC, ESCA, PAAD, SARC, STAD, BRCA) except COAD.…”
Section: Discussionmentioning
confidence: 99%